Genome-wide analysis of WRKY transcription factors involved in abiotic stress in Lonicera japonica - Li, Zhihui; Pi, Bing; Liu, Sisi; Li, Yongxin; Cai, Neng; Peng, Jiqing; Liu, Chong; Qiao, Zhongquan (Frontiers in Plant Science, 2025)
The WRKY transcription factor family, one of the largest gene families in plants, plays crucial roles in regulating growth, stress responses, and environmental adaptation. However, the specific functions and regulatory mechanisms of WRKY genes in Lonicera japonica (honeysuckle) under drought and salt stress remain poorly characterized. In this study we identified 41 LjWRKY genes from the L. japonica genome. These genes are unevenly distributed across nine chromosomes. Phylogenetic analysis based on the conserved WRKY domain classified the LjWRKYs into Groups I, II, and III. Promoter analysis revealed an abundance of light-responsive elements, hormone-related elements and abiotic stress-related elements within the LjWRKY genes. Analysis of gene duplication events identified 70 gene pairs under strong purifying selection during evolution. Notably, comparisons with Lonicera macranthoides revealed 5 genes exhibiting exceptionally strong conservation (Ka/Ks < 0.1), suggesting potential roles as housekeeping genes. Two LjWRKY genes (LjWRKY22 and 31) were identified as key regulators through correlated expression patterns with stress-responsive physiological biomarkers. This study elucidates key regulatory mechanisms of LjWRKY transcription factors in L. japonica ‘s response to drought and salt stress. Our findings provide specific candidate genes for further investigation into WRKY functional evolution and offer a molecular basis for developing enhanced drought- and salt-tolerant L. Japonica cultivars.